Mitigation Strategy For Subsidized Mortgage Financing at Bank Sumut Syariah Medan Ringroad Sharia Branch Office - siregar, shofwan hafiz; Ahmad Syakir; Daulay, Aqwa Naser (LP2M IAIN Palopo, 2025)
This study seeks to examine the mitigation strategies employed by Bank Sumut Syariah KCSy Medan Ringroad in addressing risks associated with subsidized mortgage (KPR) financing. As housing remains a fundamental human need, the demand for housing continues to rise annually in line with Indonesia’s population growth—one of the key factors driving the housing shortage. To address this, the government has initiated collaborative efforts to provide adequate housing for low-income individuals through subsidized housing schemes. These programs aim to facilitate home ownership, particularly in Medan and its surrounding regions, by offering financial support in the form of subsidized installment payments via partner banking institutions. This research adopts a qualitative approach utilizing descriptive-analytical methods. It employs a case study design centered on Bank Sumut Syariah KCSy Medan Ringroad and incorporates data triangulation to ensure the credibility and reliability of the findings. The data used in this study consists of primary data sourced from the bank itself and secondary data collected from recipients of subsidized mortgage financing. The findings indicate that the primary risk mitigation strategy implemented by the bank is Risk Reduction. The application of this strategy has proven effective, as reflected in the bank’s Non-Performing Loan (NPL) ratios: 0.62% in 2022, 0.82% in 2023, and 2.11% in 2024—all of which remain well below the 5% maximum threshold established by Indonesia’s Financial Services Authority (OJK).